Rural labor absorption efficiency in urban areas under different urbanization patterns and industrial structures: The case of China - Chen Liwen; Xiangquan Zeng; Yang Yumei (Institute for the Study of Labor (IZA), 2011)
In this paper, we use Data Envelopment Analysis (DEA) to estimate how well China's urban areas absorb migrant workers under the interaction of urbanization and industrialization. We applied an output-oriented BCC model to evaluate provincial and regional rural labor absorption efficiency in mainland China. It appears that 4 out of 31 provinces and municipals are efficient, and 2 out of 8 economic regions are efficient in absorbing migrant workers. In the southern and eastern parts of China, urban labor absorption efficiency is higher compared with the western and northern parts of China. Different urbanization patterns and industrial development strategies should be adopted in different economic areas to enhance labor absorption ability in these areas. Urban areas in many parts of China still have potential to accommodate rural migrant workers. The inter-regional flow of production factors would affect urban labor absorption efficiency.
urn:nbn:de:101:1-201201103980
Keywords: J61; R23; 330; rural labor absorption in urban areas; urbanization; industry structure; DEA; Urbanisierung; Industrialisierung; Landflucht; Regionale Arbeitsmobilität; Regionaler Arbeitsmarkt; China